2011
DOI: 10.1007/s00418-011-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 in ischemic and non-ischemic liver after selective warm ischemia/reperfusion in rat

Abstract: High mobility group box 1 (HMGB1) acts as an early mediator in inflammation and organ injury. Ischemia reperfusion (I/R) injury induces HMGB1 translocation and expression in ischemic areas. However, it is unknown whether selective warm liver I/R injury also induces the expression of HMGB1 in non-ischemic lobes. The present study aimed to test the hypothesis that selective liver I/R injury also causes HMGB1 translocation and up-regulates its expression in non-ischemic liver areas. In the present study, selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 51 publications
(77 reference statements)
5
38
0
1
Order By: Relevance
“…These events are thought to contribute to the local tissue damage and end-organ injury during I/R in various organs. Increasing evidence suggests that HMGB1 is an important mediator of I/R injury in the liver (Kamo et al, 2013; Liu et al, 2011a; Liu et al, 2014b; Tsung et al, 2007a; Tsung et al, 2005; Watanabe et al, 2005; Yang et al, 2013e), heart (Andrassy et al, 2008; Huang et al, 2007; Kaczorowski et al, 2009a; Oozawa et al, 2008; Zhai et al, 2012), kidney (Chen et al, 2011b; Chung et al, 2008; Rabadi et al, 2012; Wu et al, 2007; Wu et al, 2010), spinal cord (Esposito et al, 2009; Gong et al, 2012; Huang et al, 2011c; Wang et al, 2009c; Zhai et al, 2012; Zhou et al, 2013b), brain (Hayakawa et al, 2008a; Huang et al, 2013b; Kim et al, 2008a; Qiu et al, 2008; Schulze et al, 2013; Tang et al, 2013a), and intestine (Hagiwara et al, 2010a; He et al, 2012a; Kojima et al, 2012b; Tetteh, 2013) and triggers a potentially injurious innate immune response (Kaczorowski et al, 2009b). HMGB1 is also a biomarker of injury in human liver and kidney transplantation (Ilmakunnas et al, 2008; Kruger et al, 2009).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…These events are thought to contribute to the local tissue damage and end-organ injury during I/R in various organs. Increasing evidence suggests that HMGB1 is an important mediator of I/R injury in the liver (Kamo et al, 2013; Liu et al, 2011a; Liu et al, 2014b; Tsung et al, 2007a; Tsung et al, 2005; Watanabe et al, 2005; Yang et al, 2013e), heart (Andrassy et al, 2008; Huang et al, 2007; Kaczorowski et al, 2009a; Oozawa et al, 2008; Zhai et al, 2012), kidney (Chen et al, 2011b; Chung et al, 2008; Rabadi et al, 2012; Wu et al, 2007; Wu et al, 2010), spinal cord (Esposito et al, 2009; Gong et al, 2012; Huang et al, 2011c; Wang et al, 2009c; Zhai et al, 2012; Zhou et al, 2013b), brain (Hayakawa et al, 2008a; Huang et al, 2013b; Kim et al, 2008a; Qiu et al, 2008; Schulze et al, 2013; Tang et al, 2013a), and intestine (Hagiwara et al, 2010a; He et al, 2012a; Kojima et al, 2012b; Tetteh, 2013) and triggers a potentially injurious innate immune response (Kaczorowski et al, 2009b). HMGB1 is also a biomarker of injury in human liver and kidney transplantation (Ilmakunnas et al, 2008; Kruger et al, 2009).…”
Section: Hmgb1 and Diseasementioning
confidence: 99%
“…Serum AST levels also rise at 2 h (3910 IU/L) [52], 5 h and 24 h of reperfusion [49]. Histologically, hemorrhage [50], substantial hepatocellular necrosis [52,53], swelling of hepatocytes [53], slight sinusoidal dilation [53,54] sinusoidal congestion in the centrilobular regions [50], severe cytoplasmic vacuolization [53,54], neutrophilic infiltrates [52] and polymorphonuclear leukocyte infiltration throughout the necrotic areas and sinusoidal spaces [50] are observed. In addition, mean arterial pressure rises and remains high [51].…”
Section: Ninety Minutes Of 70% Of Irmentioning
confidence: 92%
“…Also, TNF-a mRNA expression increases at 30 min, maximizes at 6 h and decreases at 24 h after reperfusion. Finally, IL-6 mRNA levels increase significantly at 30 min and 6 h of reperfusion [53]. Recent data suggest that 70% hepatic ischemia for 90 min followed by reperfusion does not induce 50% mortality [55].…”
Section: Ninety Minutes Of 70% Of Irmentioning
confidence: 96%
“…HMGB1 can be passively released by damaged cells or actively secreted by immune cells (including activated Kupffer cells and sinusoidal endothelium cells) and acts as a mediator of inflammation [e.g., involving receptors such as RAGE (Hori et al 1995)] and the family of Toll-like receptors (e.g., Park et al 2006Park et al , 2010. In the context of liver I/R injury and associated increase of HMGB1 expression within ischemic areas and the observation that liver injury can be reduced through the use of a HMGB1 neutralizing antibody (Tsung et al 2005), Liu et al (2011) wanted to investigate HMGB1 expression in non-ischemic liver areas, applying selective warm I/R injury in the rat liver. The authors found that warm I/R injury caused also at non-ischemic sites time-dependent changes with respect to the nuclear-to-cytoplasm translocation of HMGB1 in hepatocytes and increased serum levels.…”
Section: Livermentioning
confidence: 99%